Three-dimensional ceramic network reinforced composite phase-change material with high thermal conductivity and insulation and preparation method of three-dimensional ceramic network reinforced composite phase-change material

By introducing a high-thermal conductivity three-dimensional ceramic network framework into phase change materials, the low thermal conductivity and leakage problems of phase change materials are solved, and efficient thermal management and electrical insulation performance are achieved. It is suitable for thermal management and power electronic devices of complex structures. application.

CN119220079APending Publication Date: 2024-12-31WEST ANHUI UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411331441.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The problems of low thermal conductivity and phase change leakage of existing phase change materials, as well as the difficulty in preparing three-dimensional ceramic thermal conductivity networks and the difficulty in forming complex geometric structures.

Method used

Using organic solid-liquid phase change materials and highly thermally conductive insulated inorganic fillers, combined with steady-state polymer materials, a three-dimensional ceramic network skeleton with controllable structures is prepared through 3D printing technology, a thermal conduction path of the double permeable structure is established, and composite phase change materials are enhanced. thermal management capabilities and electrical insulation properties.

Benefits of technology

The preparation of three-dimensional ceramic network enhanced composite phase change materials with high thermal insulation is achieved, which improves thermal conductivity and electrical insulation performance, simplifies the preparation process, and is suitable for thermal management of complex structures and power electronic devices applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220079A_ABST
    Figure CN119220079A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of three-dimensional ceramic network reinforced composite phase-change materials, and particularly relates to a high-thermal-conductivity and insulating three-dimensional ceramic network reinforced composite phase-change material and a preparation method thereof.The high-thermal-conductivity and insulating three-dimensional ceramic network reinforced composite phase-change material comprises an organic solid-liquid phase-change material serving as a working component, an inorganic solid-liquid phase-change material serving as a working component and an inorganic solid-liquid phase-change material serving as a working component, the polyhydric alcohols are selected from paraffin, polyethylene glycol, stearic acid and polyhydric alcohols; an encapsulating component: a steady-state polymer material selected from epoxy resin and polyurethane; the reinforcing filler is a high-thermal-conductivity insulating inorganic filler and is selected from boron nitride, aluminum oxide and silicon nitride.The preparation method has the advantages that compared with a traditional porous ceramic preparation process, controllable preparation of the high-thermal-conductivity insulating porous ceramic with a complex structure is achieved by adopting a 3D printing technology, and designability and repeatability of the structure of the high-thermal-conductivity insulating porous ceramic can be achieved easily.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of three-dimensional ceramic network reinforced composite phase change materials, and specifically relates to a three-dimensional ceramic network reinforced composite phase change material with high thermal conductivity and insulation and a preparation method thereof. Background Art

[0002] With the development of microelectronics technology and the popularity of wearable devices, the number of highly integrated and miniaturized electronic devices is increasing rapidly. The heat accumulation of these high-power density electronic components in local areas will seriously damage the reliability and service life of the equipment. In addition, the rapid development of the new energy transportation industry has made the thermal stability and safety of high energy storage density power batteries an important issue that needs to be solved in the application process. Therefore, the development of high thermal conductivity insulation materials for efficient thermal management and reliable insulation packaging has important application value.

[0003] Phase change materials are regarded as a promising thermal management material due to their significant advantages such as high latent heat, good chemical stability and suitable phase change temperature. However, they have problems of low thermal conductivity and phase change leakage in applications. For the liquid phase leakage problem, solutions include direct encapsulation, microencapsulation, porous adsorption and melt blending. For enhancing thermal conductivity, high thermal conductivity fillers can be added to improve the thermophysical properties of phase change materials. High thermal conductivity carbon and metal fillers will undoubtedly greatly reduce their electrical insulation properties while enhancing the rapid thermal response ability of composite phase change materials. The addition of inorganic ceramic fillers with high thermal conductivity and good insulation can enhance the thermal conductivity of phase change materials and improve heat dissipation efficiency while ensuring electrical insulation performance. The thermal conductivity of composite materials depends on the intrinsic thermal conductivity of the filler and the ability of the filler to form a heat conduction path in the matrix. Constructing a three-dimensional thermal conductive and insulating network in the composite material is an effective way to enhance the thermal conductivity and electrical insulation properties of the composite material. Therefore, the three-dimensional ceramic network is more suitable for enhancing the thermal conductivity of phase change materials due to its high thermal conductivity and excellent electrical insulation properties. Traditional methods for preparing three-dimensional porous ceramics include pore-forming agent method, foam plastic precursor slurry molding method, sol-gel method and particle stacking method. The ceramic networks produced generally have poor pore distribution uniformity, low sample strength, poor molding processability, and it is difficult to achieve accurate and effective molding of complex geometric structures. Summary of the invention

[0004] The purpose of the present invention is to provide a three-dimensional ceramic network reinforced composite phase change material with high thermal conductivity and insulation. The main purpose is to solve the problems of low thermal conductivity and phase change leakage of current phase change materials and controllable preparation of three-dimensional ceramic thermal conductive networks. The present invention uses organic solid-liquid phase change materials as working components, high thermal conductivity and insulation inorganic fillers and stable polymer materials as supporting matrices to prepare composite phase change materials. When the working material undergoes a phase change, the supporting material can maintain a solid shape while enhancing the thermal properties of the composite material. A structurally controllable ceramic skeleton is prepared by 3D printing technology, and a high thermal conductivity three-dimensional ceramic network is introduced into a shaped composite phase change material to prepare a three-dimensional ceramic network reinforced composite phase change material. A heat conduction path of a double percolation structure is established inside the phase change matrix, while blocking the electrical conduction path, thereby simultaneously enhancing the thermal management capability and electrical insulation performance of the composite phase change material.

[0005] To achieve the above object, the present invention provides the following technical solution: a three-dimensional ceramic network reinforced composite phase change material with high thermal conductivity and insulation, comprising:

[0006] Working component: organic solid-liquid phase change material selected from paraffin, polyethylene glycol, stearic acid and polyol;

[0007] Encapsulation component: a stable polymer material selected from epoxy resin and polyurethane;

[0008] Reinforced filler: High thermal conductivity and insulation inorganic filler, selected from boron nitride, aluminum oxide, silicon nitride;

[0009] Three-dimensional ceramic network skeleton: prepared from high thermal conductivity ceramic materials such as aluminum nitride and silicon nitride through three-dimensional modeling software and digital light-curing 3D printing technology; wherein the mass ratio of the working component to the encapsulating component is 4:6 to 8:2, the reinforcing filler accounts for 0 to 20wt% of the total mass of the working component and the encapsulating component, and the three-dimensional ceramic network skeleton is embedded in and reinforces the matrix of the composite phase change material.

[0010] Preferably, the preparation of the three-dimensional ceramic network skeleton includes: mixing a photosensitive resin, a dispersant, a ceramic powder and a photoinitiator to form a ceramic slurry, wherein the photosensitive resin includes HEMA, HDDA, and TMPTA, and the ratio thereof is HEMA: HDDA: TMPTA = 5:3:2, the dispersant is BYK-210, accounting for 1 to 5wt% of the total mass of the ceramic slurry, and the photoinitiator is TPO, accounting for 3 to 8wt% of the total mass of the ceramic slurry; using a 3D printer to print the ceramic slurry into a predetermined structure, and printing the ceramic slurry under an ultraviolet wavelength of 300 to 500nm and a light intensity of 20 to 50mW / cm 2 The secondary curing is carried out under the conditions of; after the debinding and sintering processes, the ceramic skeleton is prepared in an inert gas atmosphere, and the sintering temperature ranges from 1650 to 1750℃.

[0011] A method for preparing a three-dimensional ceramic network reinforced composite phase change material with high thermal conductivity and insulation, comprising the following steps:

[0012] 1): adding an organic solid-liquid phase change material to a stable polymer resin, stirring and dissolving at 40 to 80° C. to form a uniform mixture;

[0013] 2): Add a predetermined amount of high thermal conductivity and insulation inorganic filler to the above mixture, stir by magnetic force and disperse by ultrasonic for 20 to 40 minutes, mix well and pour into a mold to obtain a composite phase change matrix material;

[0014] 3): Add the three-dimensional ceramic network skeleton to the composite phase change matrix material, and fully mix them in a vacuum negative pressure tank for 10 to 30 minutes to allow the phase change matrix material to be fully impregnated into the three-dimensional ceramic network;

[0015] 4): Place the mixture in a vacuum drying oven and cure it at 60 to 80° C. for 6 to 10 hours to complete the preparation of the composite phase change material.

[0016] Preferably, during the printing process of the three-dimensional ceramic network skeleton, the slice thickness of the printer is set to 30 to 50 μm, and the printing time for each layer is 6 to 12 seconds.

[0017] Preferably, the debinding and sintering process includes, in a nitrogen or argon atmosphere, heating from room temperature to 300 to 400°C, keeping warm for 2 hours, then heating to 550 to 600°C, keeping warm for 2 hours, and then repeating the above process once in an air environment to complete the debinding; during sintering, heating from room temperature to 1650 to 1750°C, keeping warm for 2 hours, then cooling to 400 to 600°C at a cooling rate of 5 to 15°C / min, and finally cooling to room temperature with the furnace.

[0018] Preferably, the mass ratio of the organic solid-liquid phase change material to the stable polymer resin is 7:3, and the reinforcing filler is boron nitride, and the addition amount thereof is 10 wt % of the total mass of the working component and the encapsulating component.

[0019] It can be seen from the above technical solutions that this application has the following beneficial effects:

[0020] 1. Compared with the traditional preparation process of porous ceramics, the present invention proposes to use 3D printing technology to achieve controllable preparation of highly thermally conductive insulating porous ceramics with complex structures, which helps to achieve the designability and repeatability of its structure.

[0021] 2. The present invention proposes that inorganic fillers and three-dimensional ceramic networks construct a double percolation heat conduction path in the phase change material, which helps to achieve good heat conduction, enhance the phase change thermal response of the phase change material, and improve the thermal management efficiency of the composite phase change material.

[0022] 3. Compared with some conductive filler systems such as metals and carbon materials, the insulating ceramic thermal conductive network proposed in the present invention not only improves the thermal performance of the composite phase change material, but also improves the electrical insulation safety characteristics, which is beneficial to its application in power electronic devices.

[0023] 4. The material preparation cycle of the present invention is short, the experimental operation is relatively simple, and the prepared three-dimensional ceramic network reinforced composite phase change material has good thermal properties and electrical insulation properties, can be structurally designed according to different thermal management systems, and has a wide range of applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The figure is a flow chart of a method for preparing a composite phase change material in an embodiment of the present invention. DETAILED DESCRIPTION

[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Please see attached Figure 1 , several embodiments provided by the present invention:

[0027] A three-dimensional ceramic network reinforced composite phase change material with high thermal conductivity and insulation, comprising:

[0028] Working component: organic solid-liquid phase change material selected from paraffin, polyethylene glycol, stearic acid and polyol;

[0029] Encapsulation component: a stable polymer material selected from epoxy resin and polyurethane;

[0030] Reinforced filler: High thermal conductivity and insulation inorganic filler, selected from boron nitride, aluminum oxide, silicon nitride;

[0031] Three-dimensional ceramic network skeleton: It is made of high thermal conductivity ceramic materials such as aluminum nitride and silicon nitride through three-dimensional modeling software and digital light-curing 3D printing technology; wherein the mass ratio of the working component to the encapsulating component is 4:6 to 8:2, the reinforcing filler accounts for 0 to 20wt% of the total mass of the working component and the encapsulating component, and the three-dimensional ceramic network skeleton is embedded in and reinforced in the matrix of the composite phase change material.

[0032] Furthermore, the preparation of the three-dimensional ceramic network skeleton includes: mixing a photosensitive resin, a dispersant, a ceramic powder and a photoinitiator to form a ceramic slurry, wherein the photosensitive resin includes HEMA, HDDA, and TMPTA, and the ratio thereof is HEMA: HDDA: TMPTA = 5:3:2, the dispersant is BYK-210, accounting for 1 to 5wt% of the total mass of the ceramic slurry, and the photoinitiator is TPO, accounting for 3 to 8wt% of the total mass of the ceramic slurry; using a 3D printer to print the ceramic slurry into a predetermined structure, and under ultraviolet wavelength of 300 to 500nm and light intensity of 20 to 50mW / cm 2 The secondary curing is carried out under the conditions of; after the debinding and sintering processes, the ceramic skeleton is prepared in an inert gas atmosphere, and the sintering temperature ranges from 1650 to 1750℃.

[0033] A method for preparing a three-dimensional ceramic network reinforced composite phase change material with high thermal conductivity and insulation, comprising the following steps:

[0034] 1): adding an organic solid-liquid phase change material to a stable polymer resin, stirring and dissolving at 40 to 80° C. to form a uniform mixture;

[0035] 2): Add a predetermined amount of high thermal conductivity and insulation inorganic filler to the above mixture, stir by magnetic force and disperse by ultrasonic for 20 to 40 minutes, mix well and pour into a mold to obtain a composite phase change matrix material;

[0036] 3): Add the three-dimensional ceramic network skeleton to the composite phase change matrix material, and fully mix them in a vacuum negative pressure tank for 10 to 30 minutes to allow the phase change matrix material to be fully impregnated into the three-dimensional ceramic network;

[0037] 4): Place the mixture in a vacuum drying oven and cure it at 60 to 80° C. for 6 to 10 hours to complete the preparation of the composite phase change material.

[0038] Furthermore, during the printing process of the three-dimensional ceramic network skeleton, the slice thickness of the printer is set to 30 to 50 μm, and the printing time for each layer is 6 to 12 seconds.

[0039] Furthermore, the debinding and sintering process includes, in a nitrogen or argon atmosphere, heating from room temperature to 300 to 400°C, keeping warm for 2 hours, then heating to 550 to 600°C, keeping warm for 2 hours, and then repeating the above process once in an air environment to complete the debinding; during sintering, heating from room temperature to 1650 to 1750°C, keeping warm for 2 hours, then cooling to 400 to 600°C at a cooling rate of 5 to 15°C / min, and finally cooling to room temperature with the furnace.

[0040] Furthermore, the mass ratio of the organic solid-liquid phase change material to the stable polymer resin is specifically 7:3, and the reinforcing filler is boron nitride, and its addition amount is 10wt% of the total mass of the working component and the encapsulating component.

[0041] Embodiment 1:

[0042] Step 1: Add polyethylene glycol powder to epoxy resin, stir at 70°C to completely dissolve it, and prepare a uniform mixture of polyethylene glycol and epoxy resin with a mass ratio of 7:3 (polyethylene glycol: epoxy resin). Finally, pour the polyethylene glycol and epoxy resin mixture into a customized rubber mold to obtain a composite phase change matrix material, and use vacuum curing to prepare the composite phase change material.

[0043] Step 2: Use 3D modeling software to design the tertiary periodic minimum surface (TPMS) structure, and select the Gyroid structure ceramic network model. In the preparation process of three-dimensional Si3N4 ceramics, first, the photosensitive resin (HEMA, HDDA, TMPTA, three photosensitive resin monomers HEMA: HDDA: TMPTA = 5: 3: 2) and the dispersant (2wt% BYK-210) are fully mixed to prepare an organic carrier. 500g of silicon nitride ceramic powder is added to the organic carrier in batches and ball milled for 4 to 8h, and then the photoinitiator (5wt% TPO photoinitiator) is added and mixed for 1 to 3h to obtain a ceramic slurry. The prepared slurry is added to the printer, the slice thickness of the printer is set to 40μm, the ultraviolet wavelength is 405nm, the light intensity is 44mW / cm2, and the printing time for each layer is 10s. The prepared slurry is added to the printing tank, and the printed green body is placed in the UV curing stage for 5 minutes of secondary curing. After ultrasonic cleaning with alcohol for 5 minutes, it is placed in a tubular furnace for debinding and sintering. The debinding atmosphere is nitrogen. The temperature is raised from room temperature to 350℃ (heating rate: 0.5℃ / min), kept at 350℃ for 2 hours, and then raised from 350℃ to 600℃ (heating rate: 0.5℃ / min), and kept at 600℃ for 2 hours. After that, the same heating system is repeated once in an air environment to complete the debinding process. The sintering process is to put the debinded sample into a pressureless sintering furnace with a nitrogen atmosphere, and heat it from room temperature to 1700℃, keep it for 2 hours, and then reduce it to 500℃ at a cooling rate of 10℃ / min, and finally cool it to room temperature with the furnace for sampling.

[0044] Step 3: Add the three-dimensional porous silicon nitride ceramic sintered in step 2 to the composite phase change material matrix in step 1, and mix them thoroughly in a vacuum negative pressure tank for 20 minutes so that the phase change matrix material is fully impregnated into the three-dimensional ceramic network. Finally, place the above mixture in a vacuum drying oven for curing at a temperature of 70°C and a curing time of 8 hours.

[0045] Embodiment 2:

[0046] Step 1: Add polyethylene glycol powder to epoxy resin, stir at 70°C to completely dissolve it, and prepare a uniform mixture of polyethylene glycol and epoxy resin with a mass ratio of 7:3 (polyethylene glycol: epoxy resin). Then add 10wt% of a predetermined amount of boron nitride filler to the above mixture, and mix it thoroughly by magnetic stirring for 30 minutes and ultrasonic dispersion for 10 minutes. Finally, pour the mixture of polyethylene glycol, epoxy resin and boron nitride into a customized rubber mold to obtain a composite phase change matrix material, and use vacuum curing to prepare the composite phase change material.

[0047] Step 2: Use 3D modeling software to design the tertiary periodic minimum surface (TPMS) structure, and select the Gyroid structure ceramic network model. In the preparation process of three-dimensional Si3N4 ceramics, first, the photosensitive resin (HEMA, HDDA, TMPTA, three photosensitive resin monomers HEMA: HDDA: TMPTA = 5: 3: 2) and the dispersant (2wt% BYK-210) are fully mixed to prepare an organic carrier. 500g of silicon nitride ceramic powder is added to the organic carrier in batches and ball milled for 4 to 8h, and then the photoinitiator (5wt% TPO photoinitiator) is added and mixed for 1 to 3h to obtain a ceramic slurry. The prepared slurry is added to the printer, the slice thickness of the printer is set to 40μm, the ultraviolet wavelength is 405nm, the light intensity is 44mW / cm2, and the printing time for each layer is 10s. The prepared slurry is added to the printing tank, and the printed green body is placed in the UV curing stage for 5 minutes of secondary curing. After ultrasonic cleaning with alcohol for 5 minutes, it is placed in a tubular furnace for debinding and sintering. The debinding atmosphere is nitrogen. The temperature is raised from room temperature to 350℃ (heating rate: 0.5℃ / min), kept at 350℃ for 2 hours, and then raised from 350℃ to 600℃ (heating rate: 0.5℃ / min), and kept at 600℃ for 2 hours. After that, the same heating system is repeated once in an air environment to complete the debinding process. The sintering process is to put the debinded sample into a pressureless sintering furnace with a nitrogen atmosphere, and heat it from room temperature to 1700℃, keep it for 2 hours, and then reduce it to 500℃ at a cooling rate of 10℃ / min, and finally cool it to room temperature with the furnace for sampling.

[0048] Step 3: Add the three-dimensional porous silicon nitride ceramic sintered in step 2 to the composite phase change material matrix in step 1, and mix them thoroughly in a vacuum negative pressure tank for 20 minutes so that the phase change matrix material is fully impregnated into the three-dimensional ceramic network. Finally, place the above mixture in a vacuum drying oven for curing at a temperature of 70°C and a curing time of 8 hours.

[0049] Comparative Example 1:

[0050] Polyethylene glycol powder was added to epoxy resin and stirred at 70°C to completely dissolve it, and a uniform mixture of polyethylene glycol and epoxy resin with a mass ratio of 7:3 (polyethylene glycol: epoxy resin) was prepared. Finally, the polyethylene glycol and epoxy resin mixture was poured into a customized rubber mold to obtain a composite phase change matrix material, and vacuum curing was used to prepare the composite phase change material.

[0051] Comparative Example 2:

[0052] Add polyethylene glycol powder to epoxy resin, stir at 70°C to completely dissolve it, and prepare a uniform mixture of polyethylene glycol and epoxy resin with a mass ratio of 7:3 (polyethylene glycol: epoxy resin). Then add 10wt% of a predetermined amount of boron nitride filler to the matrix and mix it thoroughly by magnetic stirring for 30 minutes and ultrasonic dispersion for 10 minutes. Finally, pour the mixture of polyethylene glycol, epoxy resin and boron nitride into a customized rubber mold to obtain a composite phase change matrix material, and use vacuum curing to prepare the composite phase change material.

[0053] Example Latent heat of phase change (J / g) Thermal conductivity W / (m·K) Volume resistivity (Ω·cm) Example 1 108.3 1.12 <![CDATA[2.6×10 14 ]]> Example 2 94.6 1.96 <![CDATA[4.3×10 14 ]]> Comparative Example 1 127.4 0.24 <![CDATA[1.2×10 14 ]]> Comparative Example 2 115.8 0.85 <![CDATA[2.4×10 14 ]]>

[0054] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A three-dimensional ceramic network reinforced composite phase change material with high thermal conductivity and insulation, It is characterized by; including: Working component: organic solid-liquid phase change material selected from paraffin, polyethylene glycol, stearic acid and polyol; Encapsulation component: a stable polymer material selected from epoxy resin and polyurethane; Reinforced filler: High thermal conductivity and insulation inorganic filler, selected from boron nitride, aluminum oxide, silicon nitride; Three-dimensional ceramic network skeleton: prepared from high thermal conductivity ceramic materials such as aluminum nitride and silicon nitride through three-dimensional modeling software and digital light-curing 3D printing technology; wherein the mass ratio of the working component to the encapsulating component is 4:6 to 8:2, the reinforcing filler accounts for 0 to 20wt% of the total mass of the working component and the encapsulating component, and the three-dimensional ceramic network skeleton is embedded in and reinforces the matrix of the composite phase change material.

2. The high thermal conductivity and insulation three-dimensional ceramic network reinforced composite phase change material according to claim 1, characterized in that: The preparation of the three-dimensional ceramic network skeleton comprises: mixing a photosensitive resin, a dispersant, a ceramic powder and a photoinitiator to form a ceramic slurry, wherein the photosensitive resin comprises HEMA, HDDA and TMPTA, and the ratio thereof is HEMA:HDDA:TMPTA=5:3:2, the dispersant is BYK-210, accounting for 1 to 5wt% of the total mass of the ceramic slurry, and the photoinitiator is TPO, accounting for 3 to 8wt% of the total mass of the ceramic slurry; using a 3D printer to print the ceramic slurry into a predetermined structure, and printing the ceramic slurry under an ultraviolet wavelength of 300 to 500nm and a light intensity of 20 to 50mW / cm 2 The secondary curing is carried out under the conditions of; after the debinding and sintering processes, the ceramic skeleton is prepared in an inert gas atmosphere, and the sintering temperature ranges from 1650 to 1750℃.

3. A method for preparing a three-dimensional ceramic network reinforced composite phase change material with high thermal conductivity and insulation, characterized in that: The following steps are involved: 1): adding an organic solid-liquid phase change material to a stable polymer resin, stirring and dissolving at 40 to 80° C. to form a uniform mixture; 2): Add a predetermined amount of high thermal conductivity and insulation inorganic filler to the above mixture, stir by magnetic force and disperse by ultrasonic for 20 to 40 minutes, mix well and pour into a mold to obtain a composite phase change matrix material; 3): Add the three-dimensional ceramic network skeleton to the composite phase change matrix material, and fully mix them in a vacuum negative pressure tank for 10 to 30 minutes to allow the phase change matrix material to be fully impregnated into the three-dimensional ceramic network; 4): Place the mixture in a vacuum drying oven and cure it at 60 to 80° C. for 6 to 10 hours to complete the preparation of the composite phase change material.

4. The method for preparing a three-dimensional ceramic network reinforced composite phase change material with high thermal conductivity and insulation according to claim 3, characterized in that: During the printing process of the three-dimensional ceramic network skeleton, the slice thickness of the printer is set to 30 to 50 μm, and the printing time of each layer is 6 to 12 seconds.

5. The method for preparing a three-dimensional ceramic network reinforced composite phase change material with high thermal conductivity and insulation according to claim 3, characterized in that: The debinding and sintering process includes heating from room temperature to 300 to 400°C in a nitrogen or argon atmosphere, keeping the temperature for 2 hours, then heating to 550 to 600°C, keeping the temperature for 2 hours, and then repeating the above process once in an air environment to complete the debinding; during sintering, heating from room temperature to 1650 to 1750°C, keeping the temperature for 2 hours, then cooling to 400 to 600°C at a cooling rate of 5 to 15°C / min, and finally cooling to room temperature with the furnace.

6. The method for preparing a three-dimensional ceramic network reinforced composite phase change material with high thermal conductivity and insulation according to claim 3, characterized in that: The mass ratio of the organic solid-liquid phase change material to the stable polymer resin is specifically 7:3, and the reinforcing filler is boron nitride, and its addition amount is 10wt% of the total mass of the working component and the encapsulating component.

Citation Information

Cited By

  • Porous composite material combining electromagnetic shielding and thermal management as well as preparation method and application of porous composite material

    CN121057188A